Ecotoxicity Evaluation of Spent Biomixtures Used for Pesticides Degradation - Huy, Dao Văn; Hieu, Nguyen Xuan; Thao Ly, Phan Thi; Chau, Ngo Thi Tuong; Thien, Le Van (VNU Journal of Science: Earth and Environmental Sciences; Vol 36 No 3DO - 10.25073/2588-1094/vnuees.4654, 2020)
Biobed in which the biomixture is the most important element has been developed and used as a simple, cheap and high effective method to degrade residues of pesticides. However, the ecotoxicity evaluation of spent biomixtures used for pesticides degradation to manage and reuse have not been paid enough attention. In present study, the biomixture composed by the top soil: straw: spent mushroom substrate ( Pleurotus pulmonarius ) in the volumetric proportions of 1:2:1 and the culture of lignin-degrading mold strain ( Penicillium chrysogenum N2) (5% v/w) was used to degrade Cartap (100 mg/kg), Cypermethrin (100 mg/kg), Chlopyrifos (100 mg/kg) and 2,4-D (10 mg/kg) denoted by SB-Car, SB-Cyp, SB-Chlor and SB-2,4-D, respectively. The ecotoxicity evaluation of spent biomixtures was carried out using the tests with soil plants, fauna and microorganisms. The results showed that, they almost inhibited neither the growth of soil plants (GI > 0.8, germination > 90%, fresh weight > 98% of the controls) nor the nitrogen mineralization in soil (for SB-Cyp, SB-Chlor và SB-2,4-D). Also, they caused no the acute toxicity to earthworms (no significant mortality and wet biomass reduction between the controls and treatments at concentrations < 100 g/kg dry soil).